Effects of Chloroform on the Activity of Na+-K+ Atpase, Catalase, Glutathione and Malondialdehyde Levels in Human Erythrocytes - Gul, Sermin; Bilgin, Ramazan; Tukel, Seyhan (Asian Journal of Chemistry, 2010)
The objectives of this study is to assess the effects of the chloroform on erythrocytes by measuring the Na+-K+ATPase (EC.3.6.1.39) and catalase (EC 1.11.1.6) activities and also the amount of reduced glutathione and malondialdehyde. In vitro exposure of intact human erythrocytes or freshly prepared erythrocyte membranes to chloroform for different contact times (0, 6, 12, 24, 48 h) resulted in the inhibition of erythrocyte membrane Na+-K+ATPase activity in a time dependent manner. The results also indicated that catalase activity, glutathione and malondialdehyde levels were sensitive parameters for chloroform.